Gavrilovich O. G. Zoomorphic code of culture in the phraseology of the Belorussian, Russian and English languages: comparative analysis - Gavrilovich O. G. (Philological Treatises, 2020)
The article specifies the results of comparative analysis of phraseological units with zoonymic components cock, hen and goose of the Belorussian, Russian and English languages. Some stereotypical views on this fragment of the world picture of the Belorussians, Russians and English are revealed, common and distinctive figurative features of the aforementioned animals are determined.